2014
DOI: 10.1021/jf404539y
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Antidiabetic and Antihypertensive Properties of Canary Seed (Phalaris canariensis L.) Peptides

Abstract: Canary grass is used as traditional food for diabetes and hypertension treatment. The aim of this work is to characterize the biological activity of encrypted peptides released after gastrointestinal digestion of canary seed proteins. Canary peptides showed 43.5% inhibition of dipeptidyl peptidase IV (DPPIV) and 73.5% inhibition of angiotensin-converting enzyme (ACE) activity. An isolated perfused rat heart system was used to evaluate the canary seed vasoactive effect. Nitric oxide (NO), a major vasodilator ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
2
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 39 publications
(71 reference statements)
3
42
2
4
Order By: Relevance
“…Another approaches for control of diabetes are through inhibition of dipeptidyl peptidase‐IV (DPP‐IV) activity that increases the half‐life of total circulating GLP‐1 (peptides that stimulates glucose‐dependent insulin secretion in pancreatic β‐cells) by preventing it from degradation and inactivation. Thereafter, prolonged secretion of insulin resulted in more absorption of glucose by the tissues and decreased in plasma glucose (Estrada‐Salas, Montero‐Morán, Martínez‐Cuevas, González, & Barba de la Rosa, 2014; Vilcacundo et al, 2017; Zambrowicz et al, 2015). Hence, in the past few years, enzyme inhibitors have developed for control of the type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Another approaches for control of diabetes are through inhibition of dipeptidyl peptidase‐IV (DPP‐IV) activity that increases the half‐life of total circulating GLP‐1 (peptides that stimulates glucose‐dependent insulin secretion in pancreatic β‐cells) by preventing it from degradation and inactivation. Thereafter, prolonged secretion of insulin resulted in more absorption of glucose by the tissues and decreased in plasma glucose (Estrada‐Salas, Montero‐Morán, Martínez‐Cuevas, González, & Barba de la Rosa, 2014; Vilcacundo et al, 2017; Zambrowicz et al, 2015). Hence, in the past few years, enzyme inhibitors have developed for control of the type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…as an agent that protects the yarn during processing and improves cloth characteristics). Canary seed has been used as a folk medicine for diabetes and hypertension, and recent research (Estrada-Salas et al 2014) has indicated that it has some potential therapeutic value. Ground hulled canary seed is currently marketed as a powder for preparing a beverage called 'Canary Seed Milk' in Mexico and the US, but apparently for use as a traditional medicine rather than for food.…”
Section: Minor Usesmentioning
confidence: 99%
“…Currently this crop is solely used as food for caged and wild birds. However the unique composition and characteristics of Phalaris canariensis make it a promising cereal for food and industrial uses [8,9,10]. It is spread throughout the entire northern hemisphere, particularly in Asia, Europe, North America and North Africa.…”
Section: Introductionmentioning
confidence: 99%